Desenvolvimento de sistema híbrido de dióxido de titânio e alga Chlorella vulgaris imobilizados em fibra oca de alumina para a redução de cromo(VI) por fotocatálise - Costa, Igor Geraldo Fiuza (2018)
Due to the population growth, the manufacture of products has been increased and, consequently, the generation of effluents with toxic materials. Among them, the chrome stands out. At its 6+ oxidation state, chromium (Cr) is toxic and carcinogenic. Traditional chrome treatments demand a high chemical load, being important the proposal of alternative processes. Thus, sorption and photocatalysis processes have gained prominence in the scientific area due to their more sustainable aspect and good yield. In this perspective, here we propose the development of a hybrid system of titanium dioxide (TiO2) and the green alga Chlorella vulgaris immobilized on asymmetric alumina hollow fibers for the reduction of hexavalent chromium (Cr(VI)) by photocatalysis. Initially, the titanium dioxide powder was characterized by XRD, SEM and EDS, the alga was characterized by its cell growth, and the lamp used in the photo-fermentation system was characterized by its luminous spectrum. Isotherm and kinetic studies of Cr(VI) sorption in titanium and in alga were carried out. Subsequently, the fiber systems with titanium dioxide and alga were developed. Finally, the photoreduction of Cr(VI) was carried out under different conditions, altering the pH (2 and 7), the medium (water and Modified Basal Bold medium-BBM) and the photocatalyst agent (TiO2, TiO2 incorporated in the fiber, seaweed, seaweed and TiO2). Thus, it was possible to verify that the used TiO2 powder is predominantly in the crystalline anatase form, that the C. vulgaris does not present a significant lag phase and that the tungsten lamp used presents a suitable luminous spectrum for the photocatalysis process. In relation to Cr(VI) sorption processes, both were found to be favorable. The adsorption of Cr(VI) by TiO2 was better represented by the Freundlich model and its kinetics by the pseudo-second order model. The Cr(VI) biosorption by the alga was better represented by the Langmuir model and its kinetics did not present a specific model. At the evaluated conditions, the maximum sorption of Cr(VI) in TiO2 and in the alga was of 2,87±0,09 mg Cr(VI)/g TiO2 e 15,933±0,09 mg Cr(VI)/g alga. The applied methodology enabled the immobilization of TiO2 and alga in the fiber microvoids and in the fiber outer surface, respectively. Related to the photocatalysis tests with the TiO2 powder, it was verified that the pH 2 was favorable to the process, while the BBM medium, although not presenting a regular effect, was also favorable. For an initial concentration of 10 mg/L Cr(VI) and a dosage of 1g/L of TiO2, the systems with TiO2 imobilized in the fiber yielded about 95% reduction of Cr(VI) at pH 2 and water for 3 days under illumination, while pure TiO2 reduced about 90%. In relation to the tests with the alga it was possible to verify that, again, pH 2 was favorable to the photoreduction process, but unfavorable in relation to alga growth. In addition, it was possible to verify the anti-algal effect of titanium dioxide, which also impaired the photocatalysis process. Fiber with TiO2 and alga yielded a yield of about 100% Cr(VI) reduction at pH 2 and in water medium after 16 h of process. Finally, after 5 cycles of reuse, the fiber with TiO2 and alga kept its efficiency reduced by 9%, proving to be viable for the Cr(VI) photocatalysis process. Thus, the development of a hybrid system composed by TiO2 imobilized in the alumina hollow fiber microvoids with the alga C. vulgaris imobilized in the fiber outer surface showed to be a suitable alternative for Cr(VI) reduction.